Application of Learning Motivation in Islamic Education Learning in Integrated Islamic Junior High Schools (SMP IT) in an Islamic Counseling Perspective - Nunzairina, Nunzairina; Akhyar Lubis, Saiful; Nur Nasution, Wahyudin (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
The formulation of the problem of this research is, how to apply learning motivation to PAI learning in integrated Islamic junior high schools in the city of Binjai from an Islamic counseling perspective. This type of research uses descriptive qualitative. This research approach uses a phenomonological research approach. This research is classified as a type of field research, where the research objects and studies are carried out in the field. The results of this research are that institutions participate in the implementation of PAI learning, determine special teachers, namely guidance and counseling teachers and teachers who have a mandate to handle the sustainability of planned activities, and all parties in the school are obliged to follow and carry out planned activities.